Density dependence maintains long‐term stability despite increased isolation and inbreeding in the Florida Scrub‐Jay - Jeremy Summers; Elissa J. Cosgrove; Reed Bowman; John W. Fitzpatrick; Nancy Chen (Ecology Letters, 2024)
Isolation caused by anthropogenic habitat fragmentation can destabilize populations. Populations relying on the inflow of immigrants can face reduced fitness due to inbreeding depression as fewer new individuals arrive. Empirical studies of the demographic consequences of isolation are critical to understand how populations persist through changing conditions. We used a 34‐year demographic and environmental dataset from a population of cooperatively breeding Florida Scrub‐Jays ( Aphelocoma coerulescens ) to create mechanistic models linking environmental and demographic factors to population growth rates. We found that the population has not declined despite both declining immigration and increasing inbreeding, owing to a coinciding response in breeder survival. We find evidence of density‐dependent immigration, breeder survival and fecundity, indicating that interactions between vital rates and local density play a role in buffering the population against change. Our study elucidates the impacts of isolation on demography and how long‐term stability is maintained via demographic responses.